PENGARUH PENYULUHAN MENGGUNAKAN MEDIA RODA PUTAR TERHADAP PENGETAHUAN KARIES GIGI PADA MURID KELAS III DAN IV SDN GAMBUT II - Nur’aien Istiqayani Salsabila; Ida Rahmawati; Isnawati Isnawati (JURNAL TERAPIS GIGI DAN MULUT, 2020)
A children group with 8 to 10 years of aged (3 to 4 elementary school grades) is a naive and a real thinking period of time, it’s also a periode of time to gather knowledge, and a games is chosen as a tool that is in accordance with the target, so that dental and oral health education can produce behavioral changes for them as a target. The results from an observation of a preliminary study that had been done on 10 students in SDN Gambut 11, consist of 6 students from the third grade and the rest 4 students from the fourth, resulted an average def-t was 3.8 and 6.2 an average DMF-T rate. This study aims to determine whether there is an influence of counseling using a rotary wheel media on dental caries knowledge for the third and fourth grade students of SDN Gambut 11. The research design using "One Group Pretest-Posttest", Involving 56 people as a sample, with total sampling techniques followed by Paired Sample T-test used as a statistical tests. The results showed that there was an influence on counseling before and after using the rotary wheel media on dental caries knowledge. Based on the Paired Sample T-test, it was found that the value of ρ = 0.000 with α = 0.05 so ρ < α, so then Ho was rejected and Ha being accepted. Research concluded there has an influence of counseling using rotary media on dental caries knowledge in third and fourth grade of SDN Gambut 11 studens. It is recommended to estblished a promotion activities like dental caries counseling by local health center officers or teachers by using games or the other types of media in order to help elementary school children to increase the dental caries knowledgement.